Scrutinizing the patients with breast lump on fine needle aspiration cytology - Samad, Afra; Fayyaz, Nudrat; Ali, Kanwar Sajid; Ashraf, Aqsa; Mahmood, Namra; Kashif, Muhammad (International Journal Of Community Medicine And Public Health, 2019)
Background: One of the most common medical problems, women face today, is a lump in the breast. These lumps may range from simple inflammatory to malignant. In case of carcinoma, early and accurate diagnosis can save the patient from metastases thus reducing mortality and morbidity. The aim of the present study is to see the spectrum of lesion in breast lump specimens in Ibn e Sina Hospital, Multan Medical and Dental College, Multan over a period of ten years. Methods: This retrospective study was carried out in the Department of Pathology, Multan Medical and Dental College Multan, Pakistan. Data were gathered from the archives of Pathology laboratory, comprising of years 2007 t0 2017, after approval from Institutional Ethical Review Committee. All the patients presented with complaint of any kind of swelling of breast were included in this study. All the demographic and clinical details of the patients were collected on proforma. Fine needle aspiration technique was used to take sample from the suspected lesional area. Descriptive statistics was used to analyze the data. Results: A total of 2039 patients were presented with complaint of lump/swelling in their breast unilaterally or bilaterally. There were 628 (30.8%) benign lesions, 872 (42.8) malignant lesions, 229 cases with atypical cells. Mastitis/inflammatory lesions were seen in 167 (8.2%) cases and tuberculous granulomas were observed in 83 (4.07%) cases. Twenty cases were of miscellaneous types including lipoma, phylloda, simple cysts etc. Conclusions: Findings of present study show that majority of breast lumps were malignant, benign, inflammatory and tuberculous respectively.